Analysis of Shopping Lifestyle, Discount and Online Customer Review of Impulse Buying in Shopee Live Consumers in Semarang City - Cahyani, Nur Indah; Jumai, Jumai (Economics and Business International Conference Proceeding, 2024)
The purpose of this study is to determine whether or not there is a positive or negative influence on shopping lifestyle, discounts and online customer reviews on impulse buying in Shopee Live Semarang City consumers both partially and simultaneously. The method used in this study is a quantitative method involving 96 respondents who are Shopee Live consumers in Semarang City. The research was carried out by sampling through a nonprobability sampling technique with a type of purposive sampling. The analysis technique used in this study is SPSS version 25. The results of the analysis show that Shopping Lifetyle (X¬1) has a positive and significant effect on Impulse Buying (Y), Discount (X¬2) has a positive and significant effect on Impulse Buying (Y), Online Customer Review (X¬3) has a positive and significant effect on Impulse Buying (Y), and simultaneously Shopping Lifestyle (X1), Discount (X2), and Online Customer Review (X¬3) have a positive and significant effect on Impulse Buying (Y) on Shopee Live consumers in Semarang City.